2016
DOI: 10.1007/s00432-016-2276-3
|View full text |Cite
|
Sign up to set email alerts
|

L1CAM: amending the “low-risk” category in endometrial carcinoma

Abstract: The current definition of "low-risk" in endometrial carcinoma should be amended. "Low-risk carcinomas" should be limited to L1CAM-negative tumours. L1CAM status will play a key role in future algorithms to tailor adjuvant treatment and patient follow-up strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 27 publications
4
37
0
Order By: Relevance
“…Together with our finding that L1CAM overexpression is associated with a worse outcome in the important MMR‐D and p53wt groups suggests it may have value within those subtypes, but further validation is required. It should be noted that there are very few tumours with L1CAM overexpression in the MMR‐D and p53wt groups (7 and 6%, respectively), which limits our power to validate previous studies demonstrating the prognostic significance of L1CAM among low‐risk tumours .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Together with our finding that L1CAM overexpression is associated with a worse outcome in the important MMR‐D and p53wt groups suggests it may have value within those subtypes, but further validation is required. It should be noted that there are very few tumours with L1CAM overexpression in the MMR‐D and p53wt groups (7 and 6%, respectively), which limits our power to validate previous studies demonstrating the prognostic significance of L1CAM among low‐risk tumours .…”
Section: Discussionmentioning
confidence: 80%
“…Our objective in this study was to re-evaluate select molecular markers of purported prognostic significance: L1-cell adhesion molecule (L1CAM) [14][15][16], progesterone receptor (PR) [17][18][19], estrogen receptor alpha (ER) [18][19][20], stathmin (STMN) [21,22], and phosphatase and tensin homolog (PTEN) [23,24], assessing their value in the framework of modern molecular classification (by ProMisE).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most frequently used staging systems for estimating the prognosis and risk of recurrence in thyroid carcinomas are those developed by the Union for International Cancer Control (UICC) and American Joint systems consistently include clinicopathological parameters, however, factors such as age, gender, tumor type and size, extracapsular extension, lymph nodes, lymphovascular invasion (LVI), and distant metastasis are not all covered by a single staging system [7][8][9][10][11][12][13]. Although LVI is a poor prognostic factor for numerous cancers, including laryngeal, uterine, endometrial, colorectal, cervical, bile duct, and vulvar cancer, none of the staging systems include LVI in staging of thyroid carcinomas [14][15][16][17][18][19][20]. In a clinical series conducted by Ieni et al [21], 295 PTC patients (8 of them with a newly described entity -micropapillary/hobnail variant [MPHC]) were evaluated and the authors concluded that the prognosis of MPHC-PTC tumors was better compared to the other groups, possibly due to a lower rate of vascular invasion in this group [21].…”
Section: Introductionmentioning
confidence: 99%
“…A large multicenter evaluation of L1CAM expression in early-stage type I endometrial carcinomaexpected to have excellent prognosis, with more than 80% 10-year OS -showed that despite appropriate treatment, a number of patients exhibited recurrence and poor survival and this trend was associated with L1CAM expression [16,17]. L1CAM has subsequently been proposed to be a strong prognostic factor in endometrial carcinoma and it has been suggested that the classical "low-risk" disease should potentially be further risk strati ed [18].…”
Section: Introductionmentioning
confidence: 99%